2008
DOI: 10.1111/j.1600-051x.2008.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin as an adjunctive treatment of aggressive periodontitis: 12‐months randomized clinical trial

Abstract: The adjunctive use of azithromycin has the potential to improve periodontal health of young patients with AgP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
163
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(169 citation statements)
references
References 53 publications
3
163
0
3
Order By: Relevance
“…Clinical studies have documented the presence of remaining biofilm despite good levels of plaque control. 7,8 The consumption of oral hygiene products has increased worldwide. For example, less than one toothbrush per capita was consumed in the 1990s in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have documented the presence of remaining biofilm despite good levels of plaque control. 7,8 The consumption of oral hygiene products has increased worldwide. For example, less than one toothbrush per capita was consumed in the 1990s in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that the use of systemic antimicrobial agents adjunct to mechanical periodontal treatment may be an important therapeutic strategy in the treatment of chronic [2][3][4] and aggressive [5][6][7][8][9] periodontal diseases. These results were observed with the use of different antibiotics, such as amoxicillin/metronidazole 4,[8][9][10][11] , azythromicin [12][13][14] , clindamycin 15 and clarithromycin 16 , which showed favorable results as adjunct to therapy for aggressive periodontitis and chronic periodontal disease, when compared with the control group treated with mechanical therapy alone. In addition to the effects of systemic antibiotic therapy based on the isolated use of a certain drug, the use of associations of antibiotics has also shown promising clinical and microbiological results 3,5,8,17 .…”
Section: Introductionmentioning
confidence: 68%
“…In this regard, various researchers showed that there was a significant benefit of their use as adjunct to mechanical treatment, when compared with individuals who received mechanical treatment only 5,6 . Haas et al 12 (2008) used an antibiotic regime of 500 mg azythromicin, once a day, for 3 days, associated with root scaling and planing, and after 12 months of follow-up, obtained significant improvement in the evaluated clinical parameters (probing depth and clinical attachment level) in comparison with the group that received mechanical therapy alone. In addition to the clinical benefits, some recent studies also reported the positive effects of the adjunct use of antibiotics on the subgingival microbiota of individuals with aggressive periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is another who presented antimicrobial clinical benefits (PD and CAL) in AP treatment when associated with the SRP for a period of 12 months. In addition, the researchers noted that this is a protocol that requires less time and dosage, which facilitates the patient's collaboration 43 .…”
Section: Antibioticsmentioning
confidence: 99%